Older adults and the appropriation and disappropriation of smartphones - Pang, Natalie (2016)
Research in recent years has focused on examining the acceptance as well as the appropriation of technologies amongst older adults, especially in how technologies alleviate issues of functional declines, loneliness, and financial difficulties brought about by ageing. Yet such studies have often overlooked meaningful appropriation or disappropriation of technologies amongst older adults. By drawing on a longitudinal study of ten older adults who were given a smartphone under a corporate social responsibility program by a telecommunications company, we followed the use of smartphones by ten older adult users using in-depth interviews lasting one to two hours each. Our findings revealed a mix of appropriation and disappropriation, which are linked to everyday technological use and routines, attitudes to technology, and social support.